Teori Kepribadian Sheldon di Era Modern - Nur Hasanah Harahap; Agung Pebrianto; Dania Riski Rahayu; Asmawati Asmawati (Departement of Mathematics Education, 2023)
Personality has been defined and explained by different psychologists in various ways. William Herbert Sheldon had his own idea about personality. He gave a theory, that a body type could be linked with the personality of that person; a fat person with a large bone structure tends to have an outgoing and more relaxed personality while a more muscular body-typed person is more active and aggressive. A slim or scrawny person with thin muscles is usually characterized as quiet or fragile. In order to f ind out its existence in today's modern world the research has been done 300 individuals of age group between 19 to 25 years of three different body types were selected and given a self -constructed questionnaire to check whether they are falling according to Sheldon's theory of Personality. It was found that the theory still require lot of research in order to prove that the body type affects the personality of individual because the result of research showed that the theory is less applicable in modern era.